THE ALL-INDIA MUSLIM LEAGUE AND PROVINCIAL CONGRESS MINISTRIES IN BRITISH INDIA IN 1937-1939 - L. A. Belousova (Гуманитарные и юридические исследования)
The unique episode in the history of colonial India - the activity of provincial Congress ministries in 1937-1939 - has been poorly highlighted in national scientiic studies. Before India gained independence the Indian National Congress, an oppositional party to the regime, having won regional elections, had a chance to prove itself in practical politics. It is the first time ever in national studies of India when the article refers to documents of Congress ministries. The pro-Hindu bias in their policy led to a rise in tensions between Hindus and Muslims, which alongside objective factors, led to the tragedy of the country's division in 1947. The topicality of the research prompts no doubt against the backdrop of the aggravation of inter-faith conflict in the contemporary world and the need to search for compromises between civilizations.